Medição e interpretação conceitual de parâmetros da qualidade de energia do prédio do cited da UFERSA - Melo Filho, Francisco Eufranor Souza de (Universidade Federal Rural do Semi-Árido, 2018)
The quality of energy studies the factors that can influence the generation, transmission and distribution of energy. The main objective of this work is to interpret in a conceptual way the energy quality parameters of the UFERSA Integrated Center for Technological Innovation of the Semi-Arid (CITED) building. In order to do so, it is necessary the theoretical knowledge about energy quality, carried out in this work, in order to evaluate well the behavior of the measured parameters and to provide a basis on the subjects addressed. The measurements were made using a TES - 3600 energy analyzer, divided into three different days, in order to measure: voltage, current, frequency, active power, reactive power, apparent power factor. The results were obtained in a way that made possible the study of the variations of the loads present in the building being possible to describe the characteristics that can alter the values of the parameters studied.
Keywords: Qualidade de energia; Parâmetros elétricos; Qualidade de energia elétrica no Brasil; Fator de potência; Energy quality; Electric parameters; Electric power quality in Brazil; Power factor; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA